Hypnoteaching In Islamic Law Learning - Nurul Istiani; Athoillah Islamy (Paedagogia: Jurnal Pendidikan, 2019)
This study aims to find the implementation of hypnoteaching method in fiqh (Islamic law) learning in Madrasah Tsanawiyah NU Sunan Kalijaga, Adiwerna Tegal, Central Java. This research is a qualitative research, which is a case study. Data sources of this research are interviews and varius literature on hypnoteaching. There are two big conclusions in this research. First, the hypnoteaching method is a learning method that involves cognitive, affective and psychomotor aspects of students through positive suggestions. Second, the application of hypnoteaching fiqh learning in the field works effectively related to the synergy between the principles of hypnoteaching and the existing implementation plan of learning. However, there are still inhibiting factors, namely the minimum number of teachers who have competence in the application of hypnoteaching.